SOUND ENCODING AND SYLLABLE BLENDING GAME: FUN LITERACY LEARNING FOR REMEDIAL STUDENTS (Proceedings of International Conference on Special Education, 2015)
Teaching remedial students basic literacy skills continue to challenge teachers due to students’ short attention span and memory deficits. The conventional method of teaching Malay syllable sounds by memorising the combination of letters are difficult and tedious for these students with special needs. In the teaching practicum, the second author found two of her remedial students having difficulty reading words with simple syllable sounds even after 2 years in schools. Thus, an action research was conducted with these students as the research participants. Instead of using the conventional method, the authors decided to teach Malay sound awareness followed by teaching letters which represent the sounds using animated association approach. The participants were first taught the 6 vowel sounds in Malay using 6 interesting animated songs devised by the first author based on the Malay Early Literacy Instructional Model. The students were very much attracted by the fun videos and could easily remember letters (codes) which represented the respective vowel sounds. Next, students were introduced to five consonant sounds (sonorants). Subsequently, sound blending was taught using an animation game (Plant and Grow) designed by the second author. Through this method, instead of memorising 30 syllable sounds (5 consonants x 6 vowels), participants need to only recognise 11 phoneme-grapheme correspondences to form 30 syllable sounds without tedious memorisation but acquisition of sound blending skills. Significant improvement was seen in both participants in their phonemic awareness, phonemegrapheme correspondence, syllable reading and word reading tests conducted right before and immediately after only three weeks’ intervention. Most importantly, these students regained confidence and interest in literacy learning. The findings suggest that reading and spelling can be taught through fun and easy sound coding to ease the cognitive processing load of remedial students.